Inserções e aplicabilidades do moodle como ferramenta de gestão educacional - Duraczinski, Veridiana Pereira (2015)
This paper discusses research on Insertion and applicability of Moodle as Educational Management tool, as it sought to build a form of communication with interaction and interactivity between the Municipal Agudo - RS and the directors of municipal schools. Held first a literature review on the prospects of many authors who present concepts coming to clarify and understand the research problem, which is to identify what are the limits and possibilities of integration and applicability Moodle as Educational Management tool facilitator of interaction and interactivity. Following the analysis of the application and insertion of this Educational Management tool, approaching the communication of directors of municipal schools of Agudo - RS with the City Department of Education. The work is divided into three chapters that cover from the context, conceptualization and analysis of the application and integration of Moodle in this reality. Followed by referrals Methodological and Theoretical presenting authors such as Castells (2003/2013), Okada (2003), Taspscott & Williams (2007), Nakamura (2009), Son (2014), among others that cause reflection on this issue to seek Moodle integration as Educational Management tool. Besides deepening the study on the importance of the new features, increasingly present in the school context, then the Virtual Environment Teaching and learning Moodle, can present the advantages of its use in education, going beyond the classroom, seeking understanding that there are tools which can contribute positively on the relationship between the actors involved in the educational context of a municipality. To this end, this analysis and research was based on a set of variables that include the study and understanding of interaction and interactivity in educational management processes. Concluding that when thinking about the limits and possibilities of insertion and the applicability of Moodle as Educational Management Tool facilitator of interaction and interactivity in Educational Management processes, one can see how Moodle can be important and help exchange and search for information, coming from the fields for the educational context. The final product will be the Moodle environment created to be explored and used by the Department of Education and its directors, serving as basis for other municipalities and / or researchers to make this insertion and applicability of Moodle as an educational management tool, promoting communication between educational actors. Thus, the final product of this research was the creation and implementation of the Virtual Environment Moodle as Educational Management tool because when applying found the possibility of using this feature in other Departments, not only the Department of Education and still completing the participation of a larger number of participants. The final product was the atmosphere created and used by the Municipal Education Agudo - RS and the directors of the eight public schools, in which we sought behold, educational, pedagogical, administrative and informative. The same can be used for research and basis for application in other sectors or in other municipalities.